Automatic Water Dispenser (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2026)
This article describes the structure and operating principle of an automatic water dispenser based on an infrared sensor and a microcontroller. The device provides automatic water dispensing by detecting the user's movement without contact. The article analyzes in detail the functions of the main components of the automatic water dispenser system, including the IR sensor, microcontroller control board, electric pump, relay module and Li-ion battery. The automatic and manual control modes of the device, energy saving, hygienic convenience and application possibilities in everyday life are also considered. The results of this study are of practical importance in the design and improvement of automated water supply devices.